Efficacy of Foliar Spray with Seven Fungicides and a Botanical to Control Scab (Elsinoe fawcettii) and Dieback (Colletotrichum gloeosporioides) Diseases of Lemon - Siddiquee, TA; Islam, MR; Aminuzzaman, FM; Faruq, AN; Islam, MM (The Agriculturists, 2012)
An investigation was conducted in a six year old lemon (Citrus limon) garden during March to September 2007 to find out the effect of foliar spray with seven fungicides and a botanical on the severity of citrus scab (Elsinoe fawcettii) and dieback (Colletotrichum gloeosporioides) of the crop. The tested fungicides were Dinthane M 45 (0.30%), Rovral 50 WP (0.10%), Bavistin 50 WP (0.10%), Champion 77 WP (0.20%), Cupravit 50 WP (0.20%), Tilt 250 EC (0.25%), Proud 250 EC (0.25%) and the botanical allamanda (Allamanda cathartica) leaf extract (1:4). The results showed that the fungicides and allamanda leaf extract are effective to achieve significant reduction in severity of scab and dieback diseases, and to increase fruit yield of lemon. The reduction of Percent Disease Index (PDI) of scab on leaf and fruit, and that of dieback ranged 26.45-83.87, 49.01-60.20 and 35.22- 58.01%, respectively after six months of first spray. The relationship of increase in fruit yield was directly and linearly correlated with percentage of reduction in severity of dieback diseases. Based on reduction of disease severity and increase of fruit yield, Allamanda leaf extract was noted as most effective material followed by Bavistin 50 WP, Tilt 250 EC, Cupravit 50 WP and Dithane M-45. Keywords: Citrus; scab; dieback; lemon; fungicide; botanical; control DOI: http://dx.doi.org/10.3329/agric.v9i1-2.9484 The Agriculturists 2011; 9(1&2): 99-105